EKSPRESI SENI BERBASIS LINGKUNGAN PESISIRAN (KAJIAN EKSPLORATIF PENGEMBANGAN DESAIN BATIK MANGROVE SEMARANG SEBAGAI WUJUD KONSERVASI) - Syakir, Syakir (Indonesian Journal of Conservation, 2018)
Semarang mangrove batik is the results of development and exploration of batik based on coastal environment especially mangrove forests. This has become a potential development of coastal batik, both as a coloring medium and as an idea to develop batik motifs. The study using qualitative method resulted in findings (1) mangrove waste, especially fruit, leaves, and stems producing different colors, can be used as eco-friendly batik coloring material which has soft, and classic monochromatic color characteristics. (2) Mangroves are also a source of ideas for developing motives with various variants of motifs, as well as motifs of trees and mangrove roots. (3) Utilization of mangrove waste as a dye for environmentally friendly batik is a manifestation of nature conservation which has an impact on the cultivation and maintenance of mangrove plants.